2017
DOI: 10.1097/aog.0000000000002212
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Medical Abortion Provided Through Telemedicine Compared With In Person

Abstract: Adverse events are rare with medical abortion, and telemedicine provision is noninferior to in-person provision with regard to clinically significant adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 11 publications
1
104
1
2
Order By: Relevance
“…Two studies, which included women ≤10 +0 GW, reported use between 0.8 and 2.6%; one study which also included women >10 +0 GW, reported antibiotic use at 9.3% (Table ) . Other reported secondary outcomes were rate of clinical visits for complications after abortion (range 14.6–24.9%), rate of heavy bleeding (range 3.4–5.2%), and emergency visits with treatment (0.15% among TM patients and 0.21% for in‐person patients, P = 0.31) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies, which included women ≤10 +0 GW, reported use between 0.8 and 2.6%; one study which also included women >10 +0 GW, reported antibiotic use at 9.3% (Table ) . Other reported secondary outcomes were rate of clinical visits for complications after abortion (range 14.6–24.9%), rate of heavy bleeding (range 3.4–5.2%), and emergency visits with treatment (0.15% among TM patients and 0.21% for in‐person patients, P = 0.31) …”
Section: Resultsmentioning
confidence: 99%
“…There were no randomised clinical trials, and most of the data came from descriptive studies and were based on self‐reported outcomes. Two observational studies assessed the safety and success rate of TM in direct comparison with in‐person care which adds to the reliability of these results . Seven of nine of the remaining studies represented study populations for whom abortion is legally restricted, meaning that no comparison group would have been accessible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some states have already managed this through an expansion of medication abortion-only services and increased use of telemedicine, which has been demonstrated to be safe and acceptable to women and to decrease travel for patients [33]. While 19 states (almost exclusively in the South and Midwest)…”
Section: Abortion Desertsmentioning
confidence: 99%
“…Providing information about medication abortion via ‘harm reduction’ services,3 4 accessing medication abortion medicines via the internet5 6 or with support from safe abortion hotlines6–8 and buying medication abortion medicines over-the-counter without a healthcare provider intermediary9 have all been shown to be safe and effective ways to access medication abortion in legally restricted settings, increasing access to a critical health service and reducing the risks and sequelae of unsafe abortion. In addition, in settings where abortion is legal, telemedicine services that connect people to providers via a video conference10 have been shown to be safe and effective, and researchers are currently assessing both direct-to-person mailing of medication abortion medicines as well as telemedicine where people seeking abortion care connect to a provider directly from their home. Information about contraception provided as part of these service modalities can assure people seeking medication abortion that they can start using a contraceptive method at whatever point during the process is convenient for them.…”
mentioning
confidence: 99%